Left ventricular pacing induced polymorphic ventricular tachycardia via the adaptive left ventricle pacing algorithm - Fouad Khalil (Clinical Case Reports, 2020)
Abstract Providers should be aware of the possibility of cardiac resynchronization therapy‐related proarrhythmia which could be life‐threatening. His‐bundle pacing may serve as an alternative, more physiological, option in the management as it preserves the normal sequence of depolarization from the septum to the lateral wall, and from endocardium to epicardium.